Pogranicze w życiu jednostki i grup społecznych – fakty i kontrowersje - Miluska, Jolanta (Człowiek i Społeczeństwo, 2018)
Borderland may be understand in the various ways. Especially important is the conception of the territorially borderland. The article contains its definitions and characteristics in the correlation with the function of border and trans-borderland. The review of research connected with the identity of borderland’s man and the influence of the borderland on its inhabitants (borderland “effect”) shows its incoherent. Author postulates the program of the further research.